A Polyphenolic Extract from Olive Mill Wastewaters Encapsulated in Whey Protein and Maltodextrin Exerts Antioxidant Activity in Endothelial Cells - Konstantina Kreatsouli; Zinovia Fousteri; Konstantinos Zampakas; Efthalia Kerasioti; Aristidis S. Veskoukis; Christos Mantas; Paschalis Gkoutsidis; Dimitrios Ladas; Konstantinos Petrotos; Demetrios Kouretas; Dimitrios Stagos (Antioxidants, 2019)
The aim of the present study was to compare maltodextrin and whey protein as encapsulation carriers for olive mill wastewater (OMWW) phenolic extract for producing antioxidant powder, by using spray drying under 17 different conditions. In some samples, gelatin was also added in the encapsulation mixture. The antioxidant activity was assessed in vitro by using the DPPH•, ABTS•+, reducing power and DNA plasmid strand breakage assays. The results showed that both materials were equally effective for producing antioxidant powder, although by using different conditions. For example, inlet/outlet temperature of the spray drying did not seem to affect the maltodextrin samples’ antioxidant activity, but whey protein samples showed better antioxidant activity at lower temperatures. Gelatin use decreased antioxidant activity, especially in whey protein samples. The two most potent samples, one encapsulated in maltodextrin and the other in whey protein, were examined for their antioxidant effects in human endothelial cells by assessing glutathione (GSH) and reactive oxygen species (ROS) levels. Both samples significantly enhanced the antioxidant molecule of GSH, while maltodextrin sample also decreased ROS. The present findings suggested both materials for encapsulation of OMWW extract for producing antioxidant powder which may be used in food products, especially for the protection from ROS-induced endothelium pathologies.